A Note on the Cost of Diversification and the Optimal Number of Activities - Gianpaolo Rossini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1985)
In this paper we want to examine market diversification and scope of production of a firm.
Keywords: 330